Factors Influencing Self-Care Practices and Blood Pressure Among Individuals with Uncontrolled Hypertension: A Cross-Sectional Study - Jariyasakulwong P; Wattanakitkrileart D; Pongthavornkamol K; Piaseu N; Roubsanthisuk W (Patient Preference and Adherence)
Pawitra Jariyasakulwong,1 Doungrut Wattanakitkrileart,1 Kanaungnit Pongthavornkamol,1 Noppawan Piaseu,2 Weranuj Roubsanthisuk3 1Department of Medical Nursing, Faculty of Nursing, Mahidol University, Bangkok, Thailand; 2Ramathibodi School of Nursing, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 3Division of Hypertension, Department of Medicine, Faculty of Medicine Siriraj Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Doungrut Wattanakitkrileart, Department of Medical Nursing, Faculty of Nursing, Mahidol University, Bangkok, Thailand, Email doungrut.wat@mahidol.ac.thIntroduction: Self-care practices are crucial for optimizing blood pressure control and are influenced by multilevel factors.Objective: To examine the influences of multilevel factors on hypertension self-care practices among individuals with uncontrolled hypertension and to determine the relationship between hypertension self-care practices and blood pressure.Methods: The study was conducted in primary, secondary, and tertiary care settings in Bangkok, selected for convenience, where individuals with uncontrolled hypertension were recruited using a convenience sampling method based on specific inclusion criteria. Data were collected using a demographic questionnaire, the Hypertension Knowledge Level Scale, the Newest Vital Sign, the Self-Efficacy to Manage Hypertension Scale, the revised Thai Multidimensional Scale of Perceived Social Support, the Communication Assessment Tool-Nurse, the Neighborhood Scales, and the Hypertensive Self-Care Activity Level Effects. The Cronbach’s alpha coefficients were 0.82, 0.84, 0.81, 0.92, 0.96, 0.73, and 0.72 to 0.96, respectively. Data were analyzed using descriptive statistics, logistic regression, and Pearson’s correlation.Results: A total of 326 participants were included and 80.1% of them had poor hypertension self-care practices. Individuals with moderate social support were 2.23 times more likely to have poor hypertension self-care practices compared to those with high social support (OR = 2.23; 95% CI = 1.11, 4.49; p-value < 0.05). Each unit increase in poorer resources was associated with a 1.05 times higher likelihood of poor hypertension self-care practices (OR = 1.05; 95% CI = 1.02, 1.09; p-value < 0.05). Four out of six domains of hypertension self-care practices—medication adherence, physical activity, smoking status, and alcohol consumption—were significantly associated with diastolic blood pressure (r = − 0.17, p < 0.01; r = − 0.11, p < 0.05; r = 0.23, p < 0.01; and r = 0.15, p < 0.05, respectively).Conclusion: Hypertension self-care practices could be improved through multilevel factors, including social support and neighborhood resources.Keywords: uncontrolled hypertension, self-care, social support, neighborhood resource